Effects of secondary orientation on crack closure behavior of nickel-based single crystal superalloys. (February 2016) - Qiu, Wenhui; He, Zhiwu; Fan, Ya-Nan; Shi, Hui-Ji; Gu, Jialin
Highlights: Crack closure behavior of a nickel-based single crystal superalloy was studied. Specimens in two orientations exhibit different cracking manners. Secondary orientation effects on crack closure behavior were found. Abstract: The crack closure behavior of a nickel-based single crystal (SC) superalloy was studied based on in-situ SEM fatigue tests. Specimens in two different secondary orientations were tested at 600 °C. A model considering the anisotropy of SC superalloys was developed to analyze crack closure behavior. The results show that specimens in two orientations exhibit different cracking modes. For specimen [0 0 1]/[0 1 0], roughness-induced crack closure effect is dominant in crack closure behavior and crack closure effect is constant during crack propagation process. However, for specimen [0 0 1]/[1 1 0], plasticity-induced crack closure effect is dominant in crack closure which becomes enhanced as crack grows.